Puppy place : Zipper - Miles, Ellen (New York, New York : Scholastic Inc., 2014)
Charles and Lizzie Peterson love puppies. Their family fosters these young dogs, giving them love and proper care, until they can find the perfect forever home. When Lizzie goes up to the mountains with her best friend, Maria, the girls think that they're going to get a break from their dog-walking business. But then Zipper shows up and Lizzie can't resist helping this adorable pup!
660L
Accelerated Reader AR
Keywords: Puppies -- Juvenile fiction; Dogs -- Juvenile fiction; Dog rescue -- Juvenile fiction; Dogs -- Fiction; Dog rescue -- Fiction; Fiction